(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate fracture union, complications, and functional recovery of the knee after arthroscopic fixation of tibial avulsion fractures of the posterior cruciate ligament. Subjects and methods: This retrospective descriptive case series included 27 patients with tibial avulsion fractures of the posterior cruciate ligament who underwent arthroscopic fixation techniques between August 2019 and August 2025. Clinical characteristics, injury classification, associated intra-articular lesions, fixation methods, fracture union, complications, and functional outcomes assessed by the Lysholm and subjective IKDC scores at the fixed time points of 3 and 6 months postoperatively were recorded and analyzed. Results: Anatomic reduction was achieved in 24/27 cases (88.9%; 95% CI 70.8% - 97.6%). Fracture union was observed in 26/27 patients at 3 months (96.3%; 95% CI 81.0% - 99.9%) and in all 27 patients at 6 months (100%; 95% CI 87.2% - 100%). Within 6 months of follow-up, no infection, popliteal neurovascular injury, fixation loosening or failure, or reoperation was recorded (0/27; 95% CI 0% - 12.8%). The mean Lysholm score increased from 80.78 ± 11.71 at 3 months to 94.04 ± 8.78 at 6 months (mean change 13.26; 95% CI 10.63 - 15.89), and the mean subjective IKDC score increased from 72.29 ± 12.17 to 91.09 ± 10.87 (mean change 18.79; 95% CI 17.18 - 20.40); both p < 0.001. Conclusion: In this case series of 27 patients, arthroscopic fixation techniques yielded favorable early outcomes, with fracture union achieved in all patients at 6 months, no prespecified complications observed during follow-up, and significant improvements in Lysholm and subjective IKDC scores between 3 and 6 months postoperatively. Further studies with larger sample sizes and more rigorous study designs are needed to evaluate the long-term safety and effectiveness of these techniques.